2016
DOI: 10.1007/jhep08(2016)163
|View full text |Cite
|
Sign up to set email alerts
|

General proof of the entropy principle for self-gravitating fluid in f (R) gravity

Abstract: The discussions on the connection between gravity and thermodynamics attract much attention recently. We consider a static self-gravitating perfect fluid system in f (R) gravity, which is an important theory could explain the accelerated expansion of the universe. We first show that the Tolman-Oppenheimer-Volkoff equation of f (R) theories can be obtained by thermodynamical method in spherical symmetric spacetime. Then we prove that the maximum entropy principle is also valid for f (R) gravity in general stati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…It is worthy noting that P 3↔4 Dyn should be considered when we obtain the coefficient C 8 Dyn of bξ term in subsequent calculation. We also have…”
Section: ∂F ∂Rmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthy noting that P 3↔4 Dyn should be considered when we obtain the coefficient C 8 Dyn of bξ term in subsequent calculation. We also have…”
Section: ∂F ∂Rmentioning
confidence: 99%
“…Verlinder suggested that the gravity is the entropy force [3]. In recent years, the proofs of the maximum entropy principle showed that the gravitational equation can be derived from the constraint equation and the maximum of total entropy [5][6][7][8][9][10]. All these researches are trying to establish a correspona e-mail: fangxj@hunnu.edu.cn b e-mail: hexiaokai77@163.com c e-mail: jljing@hunn.edu.cn dence between the first variation of thermodynamic quantities and gravitational equation.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a series of papers proved that the maximum entropy principle for a perfect fluid holds in different theories. This principle shows that if the constraint equation and some thermodynamic conditions are satisfied, the gravitational field equations could be derived by the extrema of the total entropy [3][4][5][6][7][8][9]. Recently, Jacobson proposed the "causal diamond" structure and considered entanglement equilibrium to imply the Einstein equations [10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the proof of the maximum entropy principle have shown that, for self-gravitating perfect fluid, the gravitational equation can be derived from the constraint equation and the thermodynamic relation [3][4][5][6][7]. It has been proved that this principle not only applicable to general relativity, but also to other modified gravity theories, such as Lovelock gravity and f (R) theories [8,9].…”
Section: Introductionmentioning
confidence: 99%